Trends in Extension Research in India-A Case study - Girijesh Singh Mahra, B. Kumar, Neelam Bhardwaj; Debashis Dash (Indian Journal of Extension Education, 2017)
Extension Education’ has established itself as a profession and a discipline with three important components of teaching, research and service. The extension system of India has witnessed paradigm shift from ‘production led’ to ‘farmers led’ system which in turn has transformed the researches in extension. Today, extension researches and teaching is being practiced by teachers and students in more than 70 State Agricultural Universities (SAUs), four deemed to be universities (DUs), one Central Agricultural University (CAU) and four Central Universities (CUs) with Agriculture Faculty. Furthermore, extension research is being carried out in more than 100 ICAR research institutes and State Departments. The present study outlines the trends in extension research of two leading Agricultural Institutes viz. ICAR-IARI, New Delhi and GBPUAT, Pantnagar based on indepth review of M.Sc. and Ph.D. research work at respective Institutes. The present paper also reviews the extension research published in ‘Indian Journal of Extension Education’. The findings showed that besides traditional areas of extension research new areas like ‘ecotourism’, ‘nutritional security’, ‘up scaling and out scaling of farm innovations’, ‘validation of ITK’s’ and ‘climate change adaptation’ has been picked up by extension researchers nationwide leaving aside the old notion of transfer of technology.